DETERMINATION OF THE QUALITY AND SAFETY OF REFINED SUNFLOWER OIL - RATSUK, MARIIA; YUROVA, TATYANA; BIELKA, ALINA (Herald of Khmelnytskyi National University. Technical sciences, 2023)
Ukraine is the largest exporter of sunflower oil in the world (about 40% of world exports). The high level of quality of exported food products contributes to the formation of a positive image not only of the country’s economy but also of the state as a whole. Unfortunately, there are cases when food products are characterized by low quality, health hazards, and sometimes they are simply counterfeit. Under such conditions, a comprehensive study of research into product quality, consumer protection from substandard, counterfeit, and sometimes clearly dangerous goods becomes relevant. The results of the study of quality and safety indicators of refined sunflower oils of the brands "CHUMAK" "Gold", "Generous Gift" and "Oil" are presented in the article. The analysis of completeness of marking of samples of refined sunflower oil is carried out. The availability of all necessary information provided by the Law of Ukraine "On information for consumers about food" and the current DSTU 4495: 2017 for tested samples of oils. Important characteristics of the quality of sunflower oil are organoleptic characteristics, acid, peroxide and iodine number, mass fraction of moisture and volatile substances, the content of soap, wax and waxy substances. These indicators not only characterize the nutritional value of oil, but also serve as criteria for naturalness and falsification of products. Indicators of color, transparency, taste and odor of samples of refined sunflower oil were determined. It is established that the organoleptic quality indicators of the studied samples of oils meet the requirements of DSTU 4492:2017 "Sunflower oil. Specifications". The study of physico-chemical parameters of selected oil samples allows us to state that all samples meet the requirements of the current standard. According to the results of determining the acid and peroxide number, the freshest oil of the studied is the oil of TM "CHUMAK" "Gold". The presence of residual amounts of pesticides, quatas and polycyclic aromatic hydrocarbons in the selected oil samples was investigated by high-performance liquid chromatography. The studied refined sunflower oils have been shown to be safe to use.